Islamic Insurance (Takāful): A Review Of Recent Riset and Future Directions - Ditama, Rezki Agrisa; Fauzi, Muhammad; Muid, Abdul; Mahdi, Al- (Review of Islamic Economics and Finance, 2024)
Purpose – This riset aims to review of recent riset on Takāful and highlight future riset directions..Methodology - This riset is descriptive qualitative, with the method used is a literature review. Riset data was collected or searched through the Emerald data base for the last 24 months (January 2022 – December 2023) by entering the keyword title in the search column "Takāful, Islamic Insurance", and by using content analysis as a data analysis tool.Findings - The study show that during the last 24 months there were 29 Takāful riset documents (in the form of journal articles) recorded in the Emerald data base. Riset has been analyzed and summarized into several sub-categories (streams), namely Takāful riset stream 1: policy, law, governance/performance, service, marketing, accounting. Takāful riset stream 2: Micro-Takāful. Takāful riset stream 3: creating a conceptual model. Takāful riset stream 4: basic human values/traditions and the application of behavioral theory to examine behavioral intentions. Finally, Takāful riset stream 5: effects of Takāful on economic development, inclusion and islamic finance. These findings also show an increase, especially in Takāful riset stream 1 and 4. Meanwhile in Takāful riset stream 2, 3 and 5 show the need for more efforts in this area, and the researchers have outlined the opportunities. Apart from that, very important riset, such as the application of digital technology to bring sharia issues and Takāful product innovation into practice and solutions have not been found in the Takāful riset stream so there is a gap and requires serious work for future riset.